Dual Loading Antiplatelet Therapy in Patients With Acute Coronary Syndrome and High Bleeding Risk Undergoing Percutaneous Coronary Intervention: Findings From the Improving Care for Cardiovascular Disease in China Project - Yan, Yan; Gong, Wei; Huang, Xin; Li, Siyi; Wang, Ge; Ma, Youcai; Hao, Yongchen; Liu, Jun; Nie, Shaoping (Frontiers in Cardiovascular Medicine, 2022)
OBJECTIVE Loading dose of dual antiplatelet therapy (LD) is supported by the guidelines for patients with acute coronary syndrome (ACS). However, limited data is provided in the series of high bleeding risk (HBR) patients with ACS and percutaneous coronary intervention (PCI). METHODS Using data from the Improving Care for Cardiovascular Disease in China – Acute Coronary Syndrome registry, conducted between 2014 and 2019, we stratified all ACS patients with HBR and PCI according to LD used within 24 hours of first medical contact or not. Inverse probability of treatment weighting (IPTW) and Cox proportional hazards model with hospital as random effect were used to analyze differences in in-hospital clinical outcomes: the primary efficacy endpoint was mortality, and the primary safety endpoint was bleeding. RESULTS Of 21,654 evaluable patients 14,322 (66.2%) were treated with LD, and were on average older, less likely to have comorbidities and higher hemoglobin, more often treated GPI and anticoagulant during hospitalization than those without LD. After IPTW adjustment for baseline differences, LD was associated with significantly increased risk of in-hospital mortality (1.89% vs. 1.02%; hazard ratio (HR): 1.71 [95% confidence interval 1.12, 2.42]; p<0.001) and in-hospital bleeding (3.89% vs. 3.3%; HR: 1.25 [1.03, 1.53]; p=0.03). CONCLUSIONS In ACS patients with HBR, LD was associated with an increased risk of in-hospital mortality and bleeding complications after PCI. Dedicated randomized trials with contemporary ACS management are needed to confirm these findings.